Perceived organizational support as mediator between digital social media influence on technological innovation - Abhishikta Ghosh Roy (Journal of Advanced Research in Social Sciences and Humanities, 2022)
Aim: In this research, we examine the role that knowledge workers’ perceptions of organizational support play as a moderator between the impact of their social media use and their companies’ willingness to invest in new forms of technology. Methodology: The data was analyzed using survey responses from 415 knowledge workers in Indian IT companies. Findings: These results show that digital learning benefits employees’ perceptions of their organizations’ support for their professional development. The study’s results also established a link between social media, e learning, and technological advancement. Implications/Novel Contribution: The findings of this study have far-reaching implications for knowledge workers and management in India, who may increase the perceived organizational support as a mediator between the influence of digital social media on the technological innovation of knowledge workers working in IT companies in India.